Mucopolysaccharidosis type II: Enzyme Replacement Therapy Efficiency - Nato D. Vashakmadze; Leyla S. Namazova-Baranova; Natalia V. Zhurkova; Ekaterina Yu. Zakharova; Grigory V. Revunenkov; Tina V. Lobjanidze; Marina A. Babaikina ("Paediatrician" Publishers LLC, 2020)
Mucopolysaccharidosis type II (MPS II), or Hunter syndrome, is the hereditary lysosomal storage disease caused by pathological variants in IDS gene. Such variants lead to iduronate-2-sulfatase enzyme deficiency and glycosaminoglycan catabolism disorder. Major clinical signs are central nervous system lesion, disorders of musculoskeletal system, cardiovascular and respiratory systems pathologies, hepatosplenomegaly, hearing impairment. Enzyme replacement therapy (ERT) makes it possible to adjust metabolic processes in lysosomes of many organs and tissues, to improve clinical signs due to partial restoring of the damaged enzyme function. Cardiovascular pathology is the main cause of death in patients with MPS. In this regard we have studied efficiency of ERT with idursulfase and its effects on the cardiovascular system in 55 patients with MPS II. It has been shown that ERT started from an early age can significantly improve children's condition, reduce or event prevent cardiac involvement. Treatment gaps from 1 to 7 months due to economic or organizational factors in 12 patients caused worsening course of the disease.